Effects of intermittent fasting on brain health via the gut–brain axis - Zhao, Ziqian; Geng, Wenting; Gao, Yan; Liu, Yitong; Nie, Shanjing; Yin, Qingqing (Frontiers in Nutrition, 2025)
Intermittent fasting (IF), an emerging dietary strategy alternating fasting and feeding cycles, exerts multi-modal brain protection through the regulation of the gut–brain axis. With neurological and mental disorders ranking among the top global disease burdens, IF opens new frontiers in nutritional neuroscience by modulating gut microbiota composition and metabolic pathways, offering a non-pharmacological intervention strategy. Preclinical studies reveal that IF enriches probiotics, reduces neuroinflammation, and restores intestinal barrier integrity, thereby mitigating “leaky gut”-induced cognitive decline. Similarly, the ketogenic effect of IF can improve mitochondrial efficiency, while its anti-inflammatory effect alleviates the pathological changes of multiple sclerosis by suppressing autoreactive T cells. Clinical evidence reveals that IF significantly correlates with decreased β-amyloid burden in Alzheimer’s disease (AD) transgenic models and enhanced motor performance in Parkinson’s disease (PD) patients, suggesting its multimodal neuroprotective effects. Mental health benefits are equally striking: IF rebalances the Firmicutes-to-Bacteroidetes ratio, which has been linked to anxiety and depression remission. The gut–brain axis (GBA) emerged as a pivotal mediator, with short-chain fatty acids (SCFAs) and tryptophan derivatives fostering serotonin synthesis and oxidative stress reduction. This review synthesizes preclinical and clinical evidence demonstrating how intermittent fasting modulates the gut–microbiota–metabolite–brain axis to promote neuroprotection and mental health benefits, while identifying personalized protocol optimization as a critical avenue for future research.